THE TRANSFORMATION OF ECONOMICS AND INNOVATION IN THE DIGITAL VILLAGE IN THE DEVELOPMENT OF MSMEs ADVANCED CLASSES - Mafriningsianti, Evi (Yayasan Education and Social Center, 2024)
This research explores the impact of digital transformation through the Digital Village initiative on the development of Micro, Small, and Medium Enterprises (MSMEs) in Bekasi City. Digital transformation is vital to overcoming the challenges MSMEs face, including limited market access, technology, and financial resources. Kampung Digital is a technology-based community model that provides digital infrastructure, training, and technical support to increase technology adoption and MSMEs' competitiveness. This study collects data from MSME actors and stakeholders through a qualitative approach that includes in-depth interviews, participant observation, and documentation studies. The findings show that adopting digital technology increases MSMEs' operational efficiency and market access. Technological innovation, collaboration in the innovation ecosystem, community empowerment, and digital literacy have proven to be important in the success of the Digital Village. This research provides insight into how economic transformation and innovation can support the growth of MSMEs and suggest policies to advance the Digital Village initiative as a strategy for sustainable economic growth